The Relationship Between Participating in Tahfidz Extracurricular Activities and Improving Social Skills of MTsS Al-Washliyah Medan Krio Students - Mazid, Ziana; Pasaribu, Syahrin (Jurnal Riset Ilmu Pendidikan, 2025)
The phenomenon in public schools encourages students to become Al-Qur'an memorizers, while improving their social skills. This study aims to analyze the effect of student participation in the tahfidz extracurricular at MTss Al-Washliyah Medan Krio on their social skills. The research method used is quantitative with data collection techniques in the form of observation and closed questionnaires for 19 grade XI students who participate in the tahfidz extracurricular. The results of the study showed that tahfidz activities have quite an effect on students' social skills, where 47.4% of respondents strongly agree and 36.8% agree that tahfidz improves their social skills. Conversely, only 26.3% agree that tahfidz hinders social skills. Overall, more students agreed and strongly agreed than disagreed, so it can be concluded that tahfidz extracurricular activities contribute positively to students' social skills.